PENGARUH PERSEPSI PADA PERUSAHAAN, PERSEPSI PADA WEBSITE DAN KECENDERUNGAN KEPERCAYAAN TERHADAP KEPERCAYAAN AWAL PELANGGAN TOKO ON-LINE DISCTARRA DI SURABAYA - MESACH, CHRISTINE (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Development of the internet in the business world eventually gave birth to a new transaction model, known as e-commerce. Images presented on the website offered a wide range of products, product specifications, and price. Customers who are interested in these products can directly order the required or desired products directly as well as transfer the money to make payments. Customers waiting for products shipped by the company in accordance with a predetermined time period. Who presented the company website to shop on-line form (on-line shop). This study aims to determine the effect on the company's perception, the perception on the website, and the trend of customer confidence in the initial trust on-line store in Surabaya Disctarra The population in this study were all on-line store customers Disctarra in Surabaya. The sampling technique in this study is judgment sampling is a type of selection is not random samples of the information obtained by the use of certain considerations which are generally adapted to the purpose or research problem. Analysis techniques using multiple regression analysis. Based on the calculation results obtained that firm size has an influence on the initial belief. The company's reputation had an influence on the initial belief. The ability to make adjustments have any effect on initial trust. Benefits website has an influence on the initial belief. Ease of use of the website has an influence on the initial belief. Security controls have any effect on initial trust. The tendency of the trust has an influence on the initial customer trust on-line store Disctarra in Surabaya.